Concept Understanding Analysis of Coloid Materials After Application of Joyful Learning Problem Based Learning - Muflihah, Muflihah; Supardi, Kasmadi Imam; Sumarni, Woro (Journal of Innovative Science Education, 2020)
Learning without strengthening understanding of concepts can cause misconceptions and learning to be less meaningful. This study aims to analyze students' understanding of the concept of colloidal material. The research design uses quantitative descriptive methods. The research subjects were students of class XI MIPA Islamic High School Plus Bina Insani Susukan 2018/2019 academic year. Data collection using three tier multiple choice tests. The results of data analysis showed 43% of students understood the concept, 39% of students experienced misconceptions and 15% of students in the category of lack of understanding and 3% of students guessed the answers. The highest percentage of indicators shows interpreting the data and giving examples of colloidal material. This shows that most of the students were able to interpret the data and set examples well. Problem-based learning with a joyful learning approach is enough to help students in understanding students' concepts.